Analisis Pembelajaran Ustazah untuk Meningkatkan Hafalan Al-Qur’an di Pesantren Ulumul Qur’an Mardhatillah Kota Subulussalam - Raihan (Institut Agama Islam Syubbanul Wathon Magelang, 2026)
This study investigates the pedagogical strategies employed by ustazah at Pesantren Ulumul Qur'an Mardhatillah in Gampong Belegen, Simpang Kiri, to enhance Quranic memorization through a qualitative approach involving observation, interviews, and documentation. The findings reveal a comprehensive instructional framework encompassing organizational strategies—featuring a target of three juz per semester with flexible disposition—alongside delivery and management models grounded in goal orientation, individuality, and integrity. These methods are characterized by time-horizon insights, concentration of effort, and knowledge absorption, utilizing operational components such as student-teacher interaction and sustainable routines governed by the six principles of tahliyah, takhayul, taskhin, tarkiz, tartil, and tikrar. Despite internal impediments like emotional fluctuations and external factors such as digital distractions, success is consistently achieved through tawakkul, tasmi', and diligent muraja'ah (via the Nderes method), which collectively bolster memorization retention by up to 90% for the 3 to 5 juz range.